The Role of Public Relations in Promoting Interfaith Dialogue - Dewi, Ni Putu Sinta; Idris, Haziq; Fariq, Aiman; Rudiana, Randi; D, A Zulfikar (Journal International Dakwah and Communication, 2025)
Interfaith dialogue plays a crucial role in fostering mutual understanding, social harmony, and conflict resolution in multicultural societies. Public relations (PR) serves as a strategic tool in facilitating communication between religious groups, promoting shared values, and mitigating religious tensions. Despite its significance, the role of PR in interfaith dialogue remains underexplored in academic discourse. This study aims to examine how PR strategies contribute to the success of interfaith dialogue initiatives, focusing on communication techniques, stakeholder engagement, and media influence. Employing a qualitative research approach, this study analyzes case studies of PR-driven interfaith programs and conducts in-depth interviews with public relations practitioners, religious leaders, and communication experts. Findings reveal that PR enhances interfaith dialogue by fostering transparent communication, managing religious sensitivities, and leveraging digital platforms to reach broader audiences. Strategic messaging, crisis communication, and media partnerships are identified as key components in shaping public perception and engagement in interfaith initiatives. The study concludes that effective PR practices can strengthen interfaith relations, reduce misconceptions, and build sustainable peace. These findings contribute to the growing body of knowledge on religious communication and highlight the need for further integration of PR strategies in interfaith dialogue efforts.